SOUND RECOGNITION SYSTEM FOR DUMB AND DOWN SYNDROME PERSON - Ch. Sreenadh, Dr.Arasu sivagami (International Journal of Advanced Science and Technology, 2020)
Down syndrome (DS) is one of the genetic disorders. The other name of DS is trisomy 21. Actually eachchromosome in the human body has two copies. The reason of DS disease is the occurrence of third copychromosome 21 in the human body. This particular disease affected peoples have various physical andmental challenges in their entire life. The specific peoples need individual care and concentration toachieve their capability. This disease can attack the people’s cognitive attitude and growth level. It leadsto low level to high level risk of health related problems. Various tests and screening methods are used tofind the DS disease previous birth or after birth. This paper describes about new kit for providingassistance to the affected people. Mike is used to capture the speech from the patients. The controllerprocesses the abnormal speech and converts into normal speech. This is developed with the help ofArudino controller and GSM technologies and various sensors. Real time electronic projects aredeveloped with the help of Arudino Controller. By using the system the caretakers easily identify thespeech of the disease affected people and easy to identify if they are in critical condition with the help ofsensors. In this device sound detector sensor plays a major role. This sensor is used to detect theabnormal condition of the patients.